A new species in the mealybug genus Pseudococcus Westwood (Hemiptera: Coccomorpha: Pseudococcidae) from Indonesia - Zarkani, Agustin; Watson, Gillian W.; Kaydan, Mehmet Bora (Zootaxa, 2024)
The mealybug genus Pseudococcus Westwood (Hemiptera: Coccomorpha: Pseudococcidae) contains several important agricultural and/or horticultural pests in southern Asia, where information on species diversity and distributions is still incomplete. While studying the mealybug fauna in southern Sumatra, Indonesia in 2022, an undescribed species of Pseudococcus on Piper aduncum L. (Piperaceae) was collected. The species is described as Pseudococcus iffahae Zarkani & Kaydan sp. nov.; it has similarities with P. philippinicus Williams, P. longispinus (Targioni Tozzetti) and P. odermatti Miller & Williams, with which it is compared. Photomicrographs and a taxonomic illustration of P. iffahae, and an identification key to species of Pseudococcus recorded in Indonesia, Southeast and southern Asia, are provided.